2020
DOI: 10.1037/abn0000553
|View full text |Cite
|
Sign up to set email alerts
|

Identifying bridge pathways between eating disorder symptoms and suicidal ideation across three samples.

Abstract: People with eating disorders (ED) have elevated rates of suicidal thoughts and behaviors. We used network analysis to identify symptoms that bridge EDs and suicidality, as well as central symptoms within the network, among 3 groups of adults. Participants were either (a) clinical psychiatric outpatients without current EDs (n ϭ 538), (b) clinical psychiatric outpatients with a lifetime suicide attempt (n ϭ 166), or (c) people with current EDs (n ϭ 238). Networks were jointly estimated among groups. Within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 74 publications
1
27
0
Order By: Relevance
“…(2020) identified body mistrust as the bridge symptom between ED psychopathology and variables describing the interoceptive function. Consistent with the latter study, another interoceptive symptom, pain tolerance, was found to bridge ED‐specific and suicidality symptoms (Smith et al., 2020). Studies assessing comorbidity without the bridge function analysis corroborated the role of low ability to discriminate physical sensation as the node connecting ED and general symptoms in networks conducted in people with BN (Levinson et al., 2017), AN (Cascino et al., 2019) or with mixed ED diagnoses (Smith et al., 2019).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…(2020) identified body mistrust as the bridge symptom between ED psychopathology and variables describing the interoceptive function. Consistent with the latter study, another interoceptive symptom, pain tolerance, was found to bridge ED‐specific and suicidality symptoms (Smith et al., 2020). Studies assessing comorbidity without the bridge function analysis corroborated the role of low ability to discriminate physical sensation as the node connecting ED and general symptoms in networks conducted in people with BN (Levinson et al., 2017), AN (Cascino et al., 2019) or with mixed ED diagnoses (Smith et al., 2019).…”
Section: Resultssupporting
confidence: 56%
“…The high replicability of these centrality data in people with EDs may be questioned in the light of the use of the Eating Disorders Examination Questionnaire (EDE‐Q) or interview, which was specifically developed from the cognitive behavioural model of EDs, in the majority of those studies. However, most of the networks including other psychometric assessment tools together with the EDE‐Q scores showed high centrality of overvaluation of body shape and weight (Forrest et al., 2019; Levinson et al., 2017; Meier et al., 2020; Smith et al., 2019, 2020) and high centrality of anxiety, depressive, obsessive‐compulsive or post‐traumatic stress disorder symptoms too. On the other hand, one study (Kerr‐Gaffney et al., 2020) showed that difficulties in social communications and isolation were core psychopathological symptoms in people with a current or past diagnosis of AN over and above shape and weight concerns.…”
Section: Resultsmentioning
confidence: 99%
“…In line with the application to other mental disorders, various research goals can be identified among the existing literature about network approaches to EDs, namely: validation of the transdiagnostic model of eating disorders by comparing network characteristics across ED diagnoses (DuBois et al, 2017; Forrest et al, 2018; Goldschmidt et al, 2018; Mares et al, 2021; Monteleone, Tzischinsky, et al, 2022; Solmi et al, 2018; Solmi et al, 2019); estimation of the symptom network of EDs and identification of the core symptoms (Beauchamp et al, 2021; Forbush et al, 2016; Forrest et al, 2018; Forrest, Perkins, et al, 2019; Rodgers et al, 2018; Wang et al, 2019); identification and interaction with nonspecific ED symptoms (i.e., the external field) like general psychiatric symptoms, personality traits and other clinical variables (Monteleone, Mereu, et al, 2019; Solmi et al, 2018; Solmi et al, 2019), embodiment dimensions (Cascino et al, 2019), childhood maltreatment (Liebman et al, 2021; Monteleone, Cascino, et al, 2019; Monteleone, Tzischinsky, et al, 2022; Rodgers et al, 2019), mentalizing and empathy (Monteleone et al, 2020), vulnerability factors (Vervaet et al, 2021), suicidal thoughts and behaviors (Smith et al, 2020), perfectionism and interoceptive sensibility (Martini et al, 2021), affective and metacognitive symptoms (Aloi et al, 2021; Wong et al, 2021), interoceptive awareness (Brown et al, 2020), sleep disturbance (Ralph-Nearman et al, 2021), well-being domains (de Vos et al, 2021), inflexible and biased social interpretations, socioemotional functioning (Bronstein et al, 2022); assessment of psychiatric comorbidities such as depression and anxiety (Bronstein et al, 2022; Elliott et al, 2020; Kenny et al, 2021; Levinson et al, 2017; Sahlan, Williams, et al, 2021; Smith et al, 2019), posttraumatic stress disorder (Liebman et al, 2021; Vanzhula et al, 2019), social anxiety disorder (Levinson et al, 2018a; Sahlan, Keshishian, et al, 2021), obsessive-compulsive disorder (Giles et al, 2022; Kinkel-Ram et al, 2021; Meier et al, 2020; Vanzhula et al, 2021), trait anxiety disorder (Forrest, Sarfan, et al, 2019), autism spectrum disorder (Kerr-Gaffney et al, 2020), borderline personality disorder (De Paoli et al, 2020), and alcohol misuse (Cusack et al, 2021); comparison of estimated network structures among clinical and nonclinical (Vanzhula et al, 2019),...…”
Section: Resultsmentioning
confidence: 99%
“…identification and interaction with nonspecific ED symptoms (i.e., the external field) like general psychiatric symptoms, personality traits and other clinical variables (Monteleone, Mereu, et al, 2019; Solmi et al, 2018; Solmi et al, 2019), embodiment dimensions (Cascino et al, 2019), childhood maltreatment (Liebman et al, 2021; Monteleone, Cascino, et al, 2019; Monteleone, Tzischinsky, et al, 2022; Rodgers et al, 2019), mentalizing and empathy (Monteleone et al, 2020), vulnerability factors (Vervaet et al, 2021), suicidal thoughts and behaviors (Smith et al, 2020), perfectionism and interoceptive sensibility (Martini et al, 2021), affective and metacognitive symptoms (Aloi et al, 2021; Wong et al, 2021), interoceptive awareness (Brown et al, 2020), sleep disturbance (Ralph-Nearman et al, 2021), well-being domains (de Vos et al, 2021), inflexible and biased social interpretations, socioemotional functioning (Bronstein et al, 2022);…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation